Penguatan Moderasi Beragama Melalui Media Sosial (Studi Terhadap Mahasiswa IAIN SAS Babel) - yanasari, pebri (Edugama: Jurnal Kependidikan dan Sosial Keagamaan, 2021)
Social media has an important role in strengthening religious moderation, this can be seen so enthusiastic students who skate on social media. So social media has potential in the dissemination of certain issues. This research focuses on strengthening religious moderation towards IAIN SAS Babel Students on social media used. This study presents information to students on thinking patterns and being moderate to issues circulating on social media, especially in terms of religion so that they are able to behave not only textually but are able to be contextually. This type of research, when viewed from the place of research, is classified as field research.  Meanwhile, when viewed from data analysis method, this research uses qualitative and comparative descriptive method.  The sampling method used by researchers is Non-probability while the sampling technique is Purposive Sampling (Judgment Sampling).  The result of this study is that the students showed that they have little understanding of religious moderation, regardless of a deep understanding of certain issues if it is associated in people's lives. Surely this is the basic capital for students especially at IAIN SAS Babel when surfing the social world with issues of religious moderation able to filter and intelligently absorb news or issues that are widely spread through social media. Keywords : religion, moderation, social media